BŁAGAM POMÓŻCIE

Usuń nawiasy i doprowadź wyrażenia do najprostszej postaci:
a)-(x+1)=
b)10+(x+5)=
c)3x+(2x+1)=
d)5x-(x+4)=
e)23a-(17a-6)
f)-4b+(2b-3)=
g)-(-3,9x+2)+5,1x=
h)(6,1a+3,5)+(-2,5a-1,9)=
i)-(7x-3)-(3x+4)=
j)-(x-y+2)+(-5x+y-6)=

jak umiecie to poproszę o obliczenia. potrzebne na jutro.

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-12T16:46:40+02:00
A)-(x+1)= -x-1
b)10+(x+5)= 10+x+5= 15+x
c)3x+(2x+1)= 3x+2x+1=5x + 1
d)5x-(x+4)= 5x-x-4=4x-4
e)23a-(17a-6)= 23a-17a+6 = 6a+6
f)-4b+(2b-3)= -4b +2b - 3 = -2b -3
g)-(-3,9x+2)+5,1x= 3,9x - 2 +5,1x=9x - 2
h)(6,1a+3,5)+(-2,5a-1,9)=6,1a+3,5 - 2,5a - 1,9 =3,6a + 1,6
i)-(7x-3)-(3x+4)= -7x +3 - 3x - 4= -10x -1
j)-(x-y+2)+(-5x+y-6)= -x+y-2 -5x +y -6 =-6x +2y -8


1 5 1
2010-04-12T16:46:52+02:00
A)-(x+1 )=-x-1
b)10+ (x+5 )= 10+x+5=15+x
c)3x+(2x+1 ) =5x+1
d)5x-(x+4 )=5x-x-4=4x-4